‘Understanding the impact of hotels’ operations on the tourism industry in Tobago.’ - Pollard, Keichelle (2015)
Tourism has always been at the heart of Tobago’s existence. Its significance as an economy booster is often understated and unexplored. In some extreme instances, it appears to be dormant. Tourism needs to regain its position, as the life-blood of Tobago; as the distinct feature that once characterized the island; as the window to the soul of the people of Tobago. Tourism needs to be revived! An understanding of the issues surrounding its current state must first be reached before possible solutions can be advanced. This research delves into one of the players of tourism, which is the hotels, to gain insights into the issues. The outcome of this research does in fact highlight two reasons that are causing the hotels to not fully meet tourists’ expectations. These are the measurement techniques employed by the hotels and the prevailing culture of the island. Recommendations are advanced, with the desire of improving the hotels’ mechanisms for measurement as well as to gradually improve, not only the outlook of the peoples’ attitudes, but also the governing body’s approach towards tourism